METHODOLOGICAL APPROACHES TO THE FORMATION OF MECHANISMS FOR IMPLEMENTING PUBLIC POLICY IN THE MANAGEMENT OF SOCIAL CONFLICTS IN UKRAINE - STADNIICHUK, Roman; POKOTYLOVA, Valentyna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a comprehensive analysis of methodological approaches to the formation of mechanisms for implementing public policy in the management of social conflicts in Ukraine. It is substantiated that, in the context of profound transformational processes — such as war, crisis-driven population mobilization, internal migration, the fragmentation of communities, and increasing institutional distrust — none of the analyzed approaches is sufficient on its own to ensure effective conflict resolution and sustainable public governance. A detailed examination reveals that systemic and conflictological approaches provide analytical depth for understanding the complex nature of conflicts, while the structural-functional and goal-oriented approaches offer a clear distribution of responsibilities and facilitate the organization of the policy implementation process. At the same time, the institutional approach ensures the strengthening of regulatory and procedural frameworks, and the network approach fosters the building of effective partnerships among diverse stakeholders. The adaptive approach, in turn, allows for flexibility in decision-making processes, critical for environments characterized by uncertainty and rapid change. The research emphasizes the necessity of integrating these approaches to develop multidimensional, resilient mechanisms for conflict management. Particular attention is paid to the creation of monitoring and early warning systems based on digital technologies, the development of independent centers for mediation and dialogue, the establishment of structured interaction models among national, regional, and local governance bodies, and the promotion of civil society initiatives in the area of conflict prevention and resolution. The findings demonstrate that the implementation of an integrated methodological approach can significantly enhance the capacity of Ukraine’s public policy to proactively address conflicts, transform social tensions into constructive dialogue, and promote social cohesion. These recommendations are particularly relevant for the strategic development of governance in conditions of post-conflict recovery, decentralization reforms, and democratization efforts. Thus, the proposed framework contributes to both the theoretical understanding and practical application of conflict management mechanisms within the broader context of sustainable public policy development in Ukraine.